Implementation Strategy of Tahfiz Program Management in Islamic Elementary Schools - idola, doni masria; Hendriani, Suswati; Aisyah, Devy; Hanif, Akhyar; Ardimen, Ardimen (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2024)
The problem in this research is that many parents are interested in sending their children to the Superior Islamic Primary School (IUT) Padang Sibusuk because of the Tahfiz program at this school even though the students live far from the school location. This research aims to determine the management of the Tahfiz program at the Superior Integrated Islamic Primary School (IUT) Padang Sibusuk. The aim of this research is to find out: 1) Planning for the Tahfiz Program at the Superior Integrated Islamic Elementary School (IUT) Padang Sibusuk, 2) Implementation of the Tahfiz Program at the Superior Integrated Islamic Elementary School (IUT) Padang Sibusuk. 3) Evaluation of the Tahfiz Program at the Superior Integrated Islamic Elementary School (IUT) Padang Sibusuk. This type of research is carried out qualitatively using research methodscase study (case study). The sampling technique is carried out by:Porposive Sampling. Data collection techniques use observation techniques, in-depth interviews (interviews) and documentation. The results of the Tahfiz Program Management research at the Superior Integrated Islamic Elementary School (IUT) Padang Sibusuk are: Planning for the Tahfiz program starts with student entry selection based on Al-Qur'an reading and memorization, setting student memorization targets at grade level, Tahfiz notebooks learners. The implementation of the Tahfiz Program at the Superior Integrated Islamic Elementary School (IUT) Padang Sibusuk is carried out according to the schedule prepared at each class level for 2 hours of learning in class and one hour after school, where the activity process begins with students writing down the verses to be memorized, correcting the verses by the Tahfiz teacher, students memorize the corrected verses, after the students have memorized the students continue to deposit the verses. The evaluation of the Tahfiz program at the Padang Sibusuk Superior Islamic Elementary School (IUT) has not been fully carried out as fully as possible, this is because the principal only receives reports from the Tahfiz teacher on what percentage of students have achieved the memorization target at the end of the year.